2017
DOI: 10.1016/j.jrp.2016.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Velocity explains the links between personality states and affect

Abstract: The present research examined whether perceived rate of progress toward a goal (velocity) mediated the relationships between personality states and affective states. Drawing from control theories of self-regulation, we hypothesized (i) that increased velocity would mediate the association between state extraversion and state positive affect, and (ii) that decreased velocity would mediate the association between state neuroticism and state negative affect. We tested these hypotheses in 2 experience sampling met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 54 publications
4
37
0
Order By: Relevance
“…However, by focusing on states, we examined the complementary question of why the affective and behavioral components of extraversion cohere. This approach is in line with the emerging focus in personality research on the dynamic links among various affective, behavioral, and cognitive states (e.g., Howell et al, 2016;Smillie, Wilt, et al, 2015;Wilt et al, 2016). From this perspective, our results suggest that social cognitions-specifically, perceptions of social contribution-may help to bind the affective and behavioral components of extraversion.…”
Section: Strengths Limitations and Implicationssupporting
confidence: 85%
“…However, by focusing on states, we examined the complementary question of why the affective and behavioral components of extraversion cohere. This approach is in line with the emerging focus in personality research on the dynamic links among various affective, behavioral, and cognitive states (e.g., Howell et al, 2016;Smillie, Wilt, et al, 2015;Wilt et al, 2016). From this perspective, our results suggest that social cognitions-specifically, perceptions of social contribution-may help to bind the affective and behavioral components of extraversion.…”
Section: Strengths Limitations and Implicationssupporting
confidence: 85%
“…We analyzed 4381 ESM reports from 206 participants, of which 186 also completed the baseline and 154 completed the follow-up questionnaire. On average, participants completed 21.27 ESM reports (61%, SD = 11.30) which is -although slightly lower than typical -within the range for ESM studies (e.g., Fleeson, 2001Fleeson, , 2007McCabe & Fleeson, 2016;Wilt et al, 2012;Wilt et al, 2017).…”
Section: Resultsmentioning
confidence: 81%
“…Missing ESM reports are a rather common problem in ESM research. Our compliance rate was at the lower end of the range of similar studies (Fleeson, 2001(Fleeson, , 2007Howell et al, 2017;Leikas & Ilmarinen, 2017;McCabe & Fleeson, 2016;Wilt et al, 2012;Wilt et al, 2017). Although one study indicated that missing reports are not be associated with ESM-relevant variables (Sun, Rhemtulla, & Vazire, 2019), the implications of missing reports in ESM research are currently not yet well understood.…”
Section: Limitationsmentioning
confidence: 68%
See 2 more Smart Citations